Optimal taxation, child care and models of the household - Patricia Apps; Ray Rees (Institute for the Study of Labor (IZA), 2012)
This paper presents for the first time the properties of optimal piecewise linear tax systems for two-earner households, based on joint and individual incomes respectively. A key contribution is the analysis of the interaction of second earner wage differences, variation in prices of bought-in inputs into household production in the form of child care, and domestic productivity differences as determinants of across-household heterogeneity in second earner labour supply. The analysis highlights the importance of the elasticity of substitution between parental and non-parental child care in determining the relationship between utility and income across households. A central result is that taking account of a richer and more realistic specification of household time use widens the set of cases in which individual taxation is welfare-superior to joint taxation.
Keywords: J22; H21; H24; H31; D13; 330; optimal taxation; time allocation; household production; child care; inequality; labour supply